A combined computational and experimental study of the adsorption of sulfur containing molecules on molybdenum disulfide nanoparticles. Issue 21 (20th September 2018) - Yang, Tao; Feng, Junpeng; Liu, Xingchen; Wang, Yandan; Ge, Hui; Cao, Dongbo; Li, Hao; Peng, Qing; Ramos, Manuel; Wen, Xiao-Dong; Shen, Baojian
Abstract: Abstract : Combining density functional theory calculations and temperature programmed desorption (TPD) experiments, the adsorption behavior of various sulfur containing compounds, including C2 H5 SH, CH3 SCH3, tetrahydrothiophene, thiophene, benzothiophene, dibenzothiophene, and their derivatives on the coordinately unsaturated sites of Mo27 S x model nanoparticles, are studied systematically. Sulfur molecules with aromaticity prefer flat adsorption than perpendicular adsorption. The adsorption of nonaromatic molecules is stronger than the perpendicular adsorption of aromatic molecules, but weaker than the flat adsorption of them. With gradual hydrogenation (HYD), the binding affinity in the perpendicular adsorption modes increases, while in flat adsorption modes it increases first, then decreases. Significant steric effects on the adsorption of dimethyldibenzothiophene were revealed in perpendicular adsorption modes. The steric effect, besides weakening adsorption, could also activate the S–C bonds through a compensation effect. Finally, by comparing the theoretical adsorption energies with the TPD results, we suggest that HYD and direct-desulfurization path may happen simultaneously, but on different active sites.